TOXICOLOGICAL STUDY OF MERCURIALS WITH SPECIAL REFERENCE TO SAMAGANDHA KAJJALI - Chatragun, Lagad; Dnyaneshwar, Mote; K, Apte (Asian Journal of Pharmaceutical Research and Development, 2013)
Rasashastra, a mercury centered branch of Ayurveda mainly deals with the preparation of safer metallic medicinal preparations. Among all metals described in Ayurveda, Rasa i.e. mercury has unique importance due to its wide usage and comparatively potent therapeutic efficacy. In India, mercurials have been in use since time immemorial and curing many dreadful diseases till. But in present era, therapeutic usage of mercury is strongly condemned by modern scientific community as it is heavy metal and heavy metal causes toxicity in patients. So to ensure the modern scientist and patients using Ayurveda formulations, that the mercurials are safer at therapeutic dose level, here, study of acute toxicity of Samagandha Kajjali which is said to be the weakest bond of mercury was carried out.